Kwalifikatory w słowniku Jerzego Samuela Bandtkiego – rodzaje, funkcje, frekwencja - Kaszewski, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2011)
The present text discusses the issues related to the phenomenon that is enormously important for the study of historical lexicography, namely the issue of usage notes and labelling practices used in dictionaries. The author focuses on the types of stylistic and context markers used in the dictionary compiled by J.S. Bandtkie, their differentiation and estimated frequency of application (frequency of occurrence of given markers against others), and the consistency in the application of specific solutions by the author of the dictionary. Special attention is given to some of the aspects of the use of grammatical information in J.S. Bandtkie’s work and to the consistency in using given adopted solutions. The article also includes some general remarks on the scientific merit of the dictionary, one of the most extensive, as far as the lexical resources are concerned, historical dictionaries of the Polish language.